Urinary chlorine: a potential biomarker of diuretic resistant patients. (25th November 2020) - Zegri Reiriz, I; Garcia-Coscuella, D; Moreno, T; Ortega, R; Ruiz, A; Mesado, N; Aran, F; Brossa, V; Camprecios, M; Lopez, L; Roig, E; Mirabet, S
Abstract: Background: Natriuresis is gaining growing interest in identifying diuretic resistance (DR) patients. However, it has not been proved useful beyond the first day with intravenous (iv) furosemide. Moreover, data regarding urinary chlorine (uCl) or urinary potassium (uK) are scarce. We sought to assess the urine electrolyte pattern in acute heart failure (AHF) outpatients to identify those who will present DR. Methods: Single-center prospective registry of outpatients with AHF who need iv furosemide. In visit 1 (V1), baseline spot urine sample was collected. Furosemide iv bolus plus intensification of oral diuretics were performed. In control visit (V2), baseline spot urine sample was collected and congestion data were evaluated. Urine electrolytes were assessed in relation to DR (defined as need of iv furosemide in V2 due to persistent congestion). Results: From June to December 2019, 76 patients were included: median age of 75.5 years (68.2–82), glomerular filtration 40 ml/min/1.73m 2 (29.2–59.2) and NT-proBNP 3340 ng/L (1296–7044). In V1, DR patients showed higher levels of uK and lower uNa/uK than NDR (p=0.014 and p=0.007, respectively). In V2, after a median of 6 (6–15) days of intensified diuretic treatment, uNa and uCl dropped with adequate decongestion but not in DR patients (p=0.020 and p=0.001, respectively). Thus, DR patients showed in V2 higher uCl and similar uNa than NDR (table). Conclusions: After several days of intensified diuretic treatment, uCl and uNa dropped during proper decongestion but not in DR patients, showing higher levels of uCl than NDR. Mantained levels of uCl could help to identify patients with persistent congestion. Funding Acknowledgement: Type of funding source: None